Effective heat capacity method to simulate heat difusion problems with phase change - Soares, N. (2017)
This paper presents the validation of a numerical model based on the effective heat capacity method to evaluate the heat transfer with melting/solidification of a microencapsulated phase change material (PCM) – Micronal® DS 5001 X – contained in rectangular-sectioned vertical cavities. In this method, the latent heat is modelled in the energy conservation equation as an artificially inflated specific heat within the temperature interval where phase change occurs. Due to the artificial nature of the method, particular attention is addressed to the variation of the effective (or equivalent) heat capacity with temperature in order to ensure a correct prediction of the phase change kinetics and the accurate quantification of the stored/released energy during a charging/discharging cycle of the PCM. Two variation functions were investigated: rectangular and triangular profiles. To validate the numerical results against experimental data from a preceding study, calculations were performed for three configurations of a small thermal energy storage (TES) unit, considering different boundary conditions that were specified in the numerical model as measured during the experiments. In the overall, numerical results show good agreement with experiments. However, it was concluded that the triangular function does not adequately reflect the time evolution of the phase change processes. Furthermore, it leads to a deficit in the latent heat that implies the use of a correction to accurately quantify the total energy stored/released by the PCM. With the appropriate correction, both the rectangular and the triangular approaches provide adequate predictions of the problem kinetics. These considerations must be taken into account in future applications of the effective heat capacity method.